A method for directly converting synthesis gas into polyols
By using Fe5C2 and Fe2C active components in iron-based catalysts, the problem of low selectivity for direct conversion of synthesis gas into polycarbonol is solved, and high selectivity and high efficiency are achieved Made of polycarbon alcohol.
Patent Information
- Application Number
- CN202210037095.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-01-13
AI Technical Summary
In the prior art, the selectivity of direct conversion of synthesis gas into polycarbon alcohol is low, which limits the practical application of this process.
Using an iron-based catalyst, specifically composed of Fe5C2 and Fe2C, the syngas adsorbs the active species CHx* and CO* on the catalyst, and forms polycarbon alcohols highly selectively through synergistic catalysis.
The high selectivity conversion of synthesized polycarbon alcohols is achieved at low temperature and high selectivity of synthesis gas. The selectivity of alcohol products can reach more than 40%, and polybasin alcohols can account for more than 70% of alcohols, significantly improving the selectivity of polycarbon alcohols.
Smart Images

Figure CN116478015B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for directly converting synthesis gas into polyols, and in particular to a method for converting synthesis gas into polyols with high selectivity over an iron-based catalyst. Background Art
[0002] Polyols refer to alcohol compounds containing two or more carbon atoms. As high-value chemicals, they can be widely used in fuels, fuel additives, detergents, surfactants, plasticizers, pharmaceutical intermediates and other fields. At present, polyol production mostly adopts high-carbon olefin hydroformylation and oil hydrogenation. The former is monopolized by foreign technology, and the latter relies on imported raw materials. The production cost fluctuates greatly, and domestic scale production is limited. Therefore, it is undoubtedly of great significance for my country to develop new production technologies for polyols.
[0003] The direct synthesis of polyols from syngas has attracted wide attention due to its wide range of raw material sources and flexible and adjustable products. The research on efficient catalysts remains the focus of research on this process. At present, the catalyst systems studied in this process mainly include MoS2-based catalyst systems, modified methanol synthesis catalyst systems, modified Fischer-Tropsch synthesis catalyst systems, and precious metal-based catalyst systems. Although the above catalyst systems have made progress in the direct synthesis of polyols from syngas, the low selectivity for polyols limits the practical application of this process. The low selectivity of the polyols produced by this process is related to the need for synergistic catalysis at the two active sites of the catalyst in this process. These two active sites include: (1) CO dissociation adsorption active sites, which produce CH x *active species; (2) CO non-dissociative adsorption active sites, which adsorb CO and produce CO*active species. x * undergoes CO* insertion reaction to generate polyols. How to achieve efficient catalytic synergy of the two active sites of the catalyst is a challenging problem in the current research of this process and is also a key research direction of this process. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing polyols by converting syngas with high selectivity, in view of the low selectivity of the direct conversion of syngas into polyols in the prior art. In the method, the syngas is adsorbed on the Fe5C2 active component to form active species CH x * and Fe2C active components to form active species CO*, CH x * and CO* can be effectively combined on the catalyst of the present invention to form polyols with high selectivity.
[0005] The present invention provides a method for synthesizing polyols from synthesis gas, the method being characterized in that the synthesis gas raw material is introduced into a reactor containing an iron-based catalyst to react at 150-210°C to generate polyols;
[0006] The iron-based catalyst is composed of at least Fe5C2 and Fe2C, wherein the mass content of each component is: the active component Fe5C2 content is 43-72% (preferably 57-72%), the active component Fe2C content is 15-28% (preferably 20-26%), and may or may not contain other components, and the other components are Fe3O4;
[0007] The synthesis gas is a raw gas containing carbon monoxide and hydrogen, wherein the molar ratio of H2 to CO is 0.5-10, optimized to be 2-5; the raw gas does not contain or may contain one or more of the impurity gases such as CO2, CH4, C2H6, N2, Ar, etc., and the impurity gas content is less than or equal to 30% of the total volume of the raw gas (preferably less than or equal to 10% of the total volume of the raw gas).
[0008] The iron-based catalyst adsorbs and activates CO and H2 to form CH x The active component Fe5C2 can synergistically catalyze the active component Fe2C that adsorbs and activates CO to form CO* to produce polyols.
[0009] The iron-based catalyst may also contain a structural additive, which includes one or two of SiO2 and Al2O3, and the mass ratio of the structural additive to the total of the iron-based compounds (including Fe5C2, Fe2C and Fe3O4) in the catalyst is 0-0.25:1 (preferably 0-0.05:1); the additive is added to the iron-based catalyst by mixing and grinding with the iron-based compound, or the additive is added to the iron-based catalyst by adding it to a solution in the precipitation process of preparing the iron-based compound by precipitation method.
[0010] The iron-based catalyst can be prepared by the following method A or method B:
[0011] A. Commercial iron oxide (including ferroferric oxide and / or ferric oxide) pretreatment method
[0012] Steps: (1) pre-treating commercial iron oxide powder (particle size range 2-500nm, preferably 10-100 nanometers) at 300-500°C (preferably 350-500°C) in an air atmosphere for 3-10 hours (preferably 4-8 hours) to remove impurities on the surface of the iron oxide; (2) pre-treating at 270-500°C (preferably 320-450°C) in a hydrogen flow atmosphere for 2-50 hours (preferably 5-20 hours) for reduction; (3) switching to H2 / CO gas (wherein the molar ratio of H2 to CO is 0.05-10, preferably 0.5-3) at 150-220°C (preferably 180-210°C) for 1-5 hours (preferably 1-3 hours) to complete the carbonization of the iron active component to obtain an iron-based catalyst.
[0013] B. Precipitation method
[0014] The method comprises the following steps: (1) preparing a soluble iron salt solution, wherein the iron ion concentration of the iron salt solution is 0.02 to 2.0 mol / L (preferably 0.1 to 1.5 mol / L); (2) preparing ammonia water, wherein the ammonia concentration is 1 to 10 mol / L (preferably 3 to 7 mol / L); (3) adding the ammonia water of step (2) to the iron salt solution of step (1) until the pH value of the solution changes to 9 to 10; stirring for 30 to 90 minutes, separating the precipitated product by centrifugation or filtration, and washing with distilled water until the pH value of the washed solution reaches 7 to 8, and drying the washed precipitated product at 60 to 100° C. for 6 to 24 hours; (4 ) The dried precipitate is pretreated at 290-480°C (preferably 350-450°C) in an air atmosphere for 3-10 hours (preferably 4-8 hours) to remove impurities on the surface of the iron oxide; (5) It is pretreated at 270-450°C (preferably 310-430°C) in a hydrogen flow atmosphere for 2-50 hours (preferably 4-30 hours) for reduction; (6) The H2 / CO gas (wherein the molar ratio of H2 to CO is 0.05-10, preferably 0.5-3) is switched to 150-210°C (preferably 180-210°C) for 1-5 hours (preferably 1-3 hours) to complete the carbonization of the iron active component to obtain an iron-based catalyst.
[0015] In the catalyst preparation method, the soluble iron salt refers to an iron salt compound that can be dissolved in water, preferably one or more of nitrates and acetates.
[0016] In the catalyst preparation method, the reduction step conditions are: atmospheric pressure, H2: 600-3000 mL / (h·g cat ), 270~450℃, time: 2~50h; carbonization step conditions: 1.0~7.0MPa, synthesis gas: 500~8000mL / (h·g cat ), the H2 / CO gas has a H2 / CO molar ratio of 0.05-10, preferably 0.5-3, and may or may not contain CO2, with CO2 accounting for 0-10% of the total volume of the gas.
[0017] The synthesis gas synthesis polyol reaction has a reaction temperature of 150-210°C (preferably 170-200°C), a reaction pressure of 1.0-7.0MPa (preferably 2.0-5.0MPa); a raw gas space velocity of 500-8000mL / (h·g cat ), preferably 1000 to 4000 mL / (h·g cat )).
[0018] The synthesis gas to polyol synthesis reaction can realize the low-temperature direct conversion of synthesis gas to polyol synthesis, the selectivity of alcohol products can reach more than 40%, and polyols can account for more than 70% of alcohols; the polyols refer to alcohol compounds with a carbon number of 2 to 13 and containing one hydroxyl group.
[0019] The present invention has the following characteristics:
[0020] (1) The catalyst used in the present invention is a single element Fe active component, and the catalyst preparation is simple, the selectivity is high, and the stability is good;
[0021] (2) The present invention can realize the low-temperature and high-selectivity conversion of synthesis gas into polyols, with a simple reaction device and a short process flow;
[0022] In the method, when the syngas conversion rate is lower than 210°C, high selectivity conversion to polyols can be achieved, the polyol selectivity can be controlled to be above 40%, and polyols can account for more than 70% of the alcohol products. The present invention opens up a new route for high selectivity conversion of syngas to polyols. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Product distribution diagram of polyols. In the diagram, hydrocarbon compounds refer to alkenes and alkanes with carbon numbers of 1-16, alcohol compounds refer to monohydroxy alcohol compounds with carbon numbers of 1-13, and aldehyde and ketone compounds refer to monocarbonyl aldehyde compounds and ketone compounds with carbon numbers of 3-13. DETAILED DESCRIPTION
[0024] The technical details of the present invention are described in detail by the following examples. It should be noted that the examples are only used to further illustrate the technical features of the present invention, rather than to limit the present invention.
[0025] Example 1
[0026] Preparation of precipitated iron-based catalysts and their catalytic performance
[0027] First, 0.04 mol Fe(NO3)3˙9H2O was dissolved in 50 ml water to prepare an Fe salt solution; secondly, an ammonia solution was prepared with an ammonia concentration of 1 mol / L; then, the prepared ammonia solution was gradually added to the iron salt solution until the pH value of the solution changed to 10. After stirring for 60 minutes, the precipitated product was separated by suction filtration and washed with distilled water until the pH value of the washed solution reached 8. The washed precipitated product was dried at 80°C for 12 hours; the dried precipitated product was pretreated at 350°C in an air atmosphere for 6 hours to remove impurities on the surface of the iron oxide; then, the precipitated product was treated in a hydrogen flowing atmosphere (normal pressure, H2: 600 mL / (h·g cat)) for 8 h for reduction; switching to H2 / CO synthesis gas with a molar ratio of H2 / CO = 2 (1.0 MPa, synthesis gas: 500 mL / (h·g cat )) After 5 hours of treatment at 200 ° C, an iron-based catalyst was obtained, labeled as catalyst A, and its main composition is shown in Table 6.
[0028] Catalyst A was loaded into a fixed bed reactor to test the performance of direct synthesis of polyols from syngas. The reaction conditions were: raw gas molar ratio H2 / CO = 2.0, temperature 170-210°C (specific values are shown in Table 1), pressure 4.0 MPa, raw gas space velocity 2400 mL / (h·g cat The results of the reaction performance evaluation of direct synthesis of polyols from synthesis gas are listed in Table 1.
[0029] Table 1 Reaction performance of direct synthesis of polyols from syngas over catalyst A
[0030]
[0031] Note: C in the table n H 2n+1 OH, C n H 2n O, MeOH, C 2+ OH represents alcohol compounds, non-alcohol oxygen-containing compounds, methanol, and polyols (monohydroxy polyols with 2 to 13 carbon atoms), where n = 1 to 13. n H 2n+1 OH, C n H 2n O, MeOH, C 2+ OH have the same meaning as herein.
[0032] It can be seen from the results in Table 1 that within the temperature range investigated, Catalyst A exhibits good performance in the conversion of syngas to polyols, and the selectivity of alcohol compounds in the product can be maintained above 35%. As the reaction temperature increases, the CO conversion rate increases. It can be seen from the results that the suitable reaction temperature of Catalyst A is 180-200°C.
[0033] Example 2
[0034] Preparation of iron-based catalysts by commercial iron oxide pretreatment
[0035] The ferroferric oxide with a particle size of 10 to 30 nm purchased from Shanghai Pantian Powder Material Co., Ltd. was pretreated in an air atmosphere at 450°C for 10 hours to remove impurities on the surface of the ferroferric oxide; the ferroferric oxide was pretreated in an air atmosphere at 40 ...50°C for 10 hours to remove impurities on the surface of the ferroferric oxide; the ferroferric oxide was pretreated in an air atmosphere at 400°C for 10 hours to remove impurities on the surface of the ferroferric oxide; the ferroferric oxide was pretreated in an air cat)) pre-treated for 20 h for reduction; switching to synthesis gas with a molar ratio of H2 / CO = 1 at 200 ° C (7.0 MPa, synthesis gas: 8000 mL / (h·g cat )) After 3 hours of treatment to complete the carbonization of the iron active component, an iron-based catalyst was obtained, labeled as catalyst B, whose main composition is shown in Table 6.
[0036] Catalyst B was loaded into a fixed bed reactor to test the performance of the direct synthesis of polyols from syngas. The reaction conditions were: the raw gas molar ratio H2 / CO = 4.0, the temperature was 190 °C, the pressure was 1.0-7.0 MPa (the specific values are shown in Table 2), the raw gas space velocity was 3500 mL / (h·g cat The results of the reaction performance evaluation of direct synthesis of polyols from synthesis gas are listed in Table 2.
[0037] Table 2 Reaction performance of direct synthesis of polyols from syngas over catalyst B
[0038]
[0039] It can be seen from the results in Table 2 that within the pressure range investigated, Catalyst B exhibits good performance in the conversion of syngas to polyols, and the selectivity of alcohol compounds in the product remains above 35%. As the reaction pressure increases, the CO conversion rate increases. It can be seen from the results that the appropriate reaction pressure of Catalyst B is 3.0-5.0 MPa.
[0040] Example 3
[0041] The steps of catalyst preparation and evaluation were the same as those in Example 1, except that 0.04 mol Fe(NO3)3˙9H2O in the preparation step was replaced by 0.02 mol Fe(NO3)3˙9H2O and 0.02 mol Fe(NO3)2˙6H2O. The obtained iron-based catalyst was labeled as catalyst C, and its main composition is shown in Table 6. The reaction conditions for the evaluation of catalyst C were replaced by: raw gas molar ratio H2 / CO=1.0, temperature of 200°C, pressure of 5.0 MPa, raw gas space velocity of 1000-7000 mL / (h·g cat ) (Specific values are shown in Table 3). The evaluation results of the reaction performance of direct synthesis of polyols from synthesis gas over Catalyst C are listed in Table 3.
[0042] Table 3 Reaction performance of direct synthesis of polyols from syngas over catalyst C
[0043]
[0044] From the results in Table 3, it can be seen that within the investigated space velocity range, Catalyst C exhibits good performance in the conversion of syngas to polyols. The selectivity of alcohol compounds in the product can be maintained at more than 30%, and the proportion of polyols in alcohol compounds can be as high as more than 85%. As the reaction space velocity increases, the CO conversion rate decreases. From the results, it can be seen that the appropriate reaction space velocity for Catalyst C is 3000-5000mL / (h·g cat ).
[0045] Example 4.
[0046] The steps of catalyst preparation and evaluation were the same as those in Example 1, except that 0.04 mol Fe(NO3)3˙9H2O in the preparation step was replaced by 0.04 mol Fe(NO3)2˙6H2O. The obtained iron-based catalyst was labeled as catalyst D, and its main composition is shown in Table 6. The reaction conditions for evaluation were replaced by: raw gas molar ratio H2 / CO=2.0, temperature of 190°C, pressure of 4.0 MPa, and space velocity of 2000 mL / (h·g cat The evaluation results of the reaction performance of direct synthesis of polyols from synthesis gas over catalyst D are listed in Table 4.
[0047] Example 5.
[0048] The steps of catalyst preparation and evaluation are the same as those of Example 1, except that the precipitate after drying in the preparation step is pretreated in an air atmosphere at 350°C for 6 hours to remove impurities on the surface of iron oxide; and then in a hydrogen flowing atmosphere (normal pressure, H2: 600mL / (h·g cat )) for 8 h for reduction; switch to H2 / CO synthesis gas (1.0 MPa, synthesis gas: 500 mL / (h·g cat ))200℃ for 5 hours" is replaced by "the dried precipitate is pretreated at 500℃ in air for 3 hours to remove impurities on the surface of the iron oxide; then the precipitate is pretreated at 400℃ in a hydrogen flowing atmosphere (normal pressure, H2: 2000mL / (h·g cat )) for 15 h for reduction; switch to H2 / CO synthesis gas (3.0 MPa, synthesis gas: 3000 mL / (h·g cat )) 200℃ for 5 hours", the prepared iron-based catalyst is marked as catalyst E, and its main composition is shown in Table 6. The reaction conditions evaluated were replaced by: raw gas molar ratio H2 / CO=3.0, temperature of 190℃, pressure of 4.0MPa, and space velocity of 500mL / (h·g cat The evaluation results of the reaction performance of direct synthesis of polyols from synthesis gas over catalyst E are listed in Table 4.
[0049] Example 6.
[0050] The steps of catalyst preparation and evaluation were the same as those in Example 2, except that the ferroferric oxide was replaced by purchased α-ferric oxide. The prepared iron-based catalyst was marked as F, and its main composition is shown in Table 6. The reaction conditions for evaluation were replaced by a raw gas molar ratio of H2 / CO = 5.0, 10% CO2, a temperature of 210°C, a pressure of 2.0 MPa, and a space velocity of 8000 mL / (h·g cat ), the reaction performance evaluation results of direct synthesis of polyols from syngas over catalyst F are listed in Table 4.
[0051] Example 7.
[0052] The steps of catalyst preparation and evaluation were the same as those in Example 2, except that the ferroferric oxide was replaced by purchased α-iron oxide with a particle size of 10-100 nm and Al2O3 with a particle size of 50-500 nm, wherein the mass ratio of Al2O3 to α-iron oxide was 1:4. The prepared iron-based catalyst was marked as G, and its main composition is shown in Table 6. The reaction conditions for evaluation were replaced by a raw gas molar ratio of H2 / CO=5.0, 3% CO2, a temperature of 210°C, a pressure of 3.0 MPa, and a space velocity of 2000 mL / (h·g cat ), direct synthesis of syngas over catalyst G: the reaction performance evaluation results of polyols are listed in Table 4.
[0053] Example 8.
[0054] The steps of catalyst preparation and evaluation are the same as those in Example 1, except that only 0.10 g SiO2 is added during the precipitation process in the preparation step (0.01 g SiO2 is added to the prepared iron salt solution before adding ammonia water to the iron salt solution, and then the prepared ammonia water is gradually added to the iron salt solution until the pH value of the solution changes to 10). The prepared iron-based catalyst is marked as H, and its main composition is shown in Table 6. The reaction conditions for evaluation are replaced by a raw gas molar ratio of H2 / CO=2.0, 3% CO2, a temperature of 180°C, a pressure of 4.0 MPa, and a space velocity of 1000 mL / (h·g cat ), the reaction performance evaluation results of direct synthesis of polyols from syngas over catalyst H are listed in Table 4.
[0055] Table 4 Reaction performance of direct synthesis of polyols from syngas over iron-based catalysts
[0056]
[0057]
[0058] From the results in Table 4, it can be seen that catalyst DH exhibits good performance in the conversion of syngas to polyols, the selectivity of alcohol compounds in the product can be maintained at 30-40%, and the proportion of polyols in alcohol compounds can be as high as 85%. Among them, the carrier (Al2O3 and SiO2) is conducive to hydrogenation, which increases the proportion of total alcohols in total oxygen-containing compounds.
[0059] Example 9.
[0060] The evaluation conditions are as follows: the raw gas molar ratio H2 / CO=2.0, the temperature is 180°C, the pressure is 4.0 MPa, the space velocity is 4000 mL / (h·g cat ) was used to investigate the stability of the reaction performance of catalyst A for direct synthesis of polyols from synthesis gas, and the evaluation results are listed in Table 5.
[0061] Table 5 Reaction stability of direct synthesis of polyols from syngas over iron-based catalysts
[0062]
[0063] It can be seen from the results in Table 5 that catalyst A exhibits good reaction stability for the conversion of syngas to polyols, the selectivity of alcohol compounds in the product remains above 37%, and the proportion of high-carbon alcohols in the alcohol compounds can be maintained above 77%.
[0064] Example 10
[0065] Catalyst AH was characterized by X-ray diffraction spectrum, Mössbauer spectrum and elemental analysis to determine the phase and composition of the catalyst. The results are listed in Table 6.
[0066] Table 6 Phase composition of iron-based catalyst
[0067]
[0068] Agent: refers to SiO2 or Al2O3.
[0069] As can be seen from Table 6, the composition of the prepared iron-based catalyst is mainly Fe5C2 and Fe2C crystalline phases. The Fe5C2 active component is responsible for the adsorption and dissociation of CO into CH x , together with the Fe2C active component responsible for the non-dissociative adsorption of CO, synergistically promotes the direct and highly selective synthesis of polyols from syngas.
[0070] Embodiment 11
[0071] The steps of catalyst preparation and evaluation were the same as those in Example 2, except that the reaction conditions were replaced by a feed gas molar ratio of H2 / CO = 2.0, a temperature of 190°C, a pressure of 4.0 MPa, and a space velocity of 2400 mL / (h·g cat), the product distribution results of direct synthesis of polyols from syngas over catalyst I are listed in Figure 1 .from Figure 1 It can be seen that the synthesis gas conversion products of the prepared Fe-based catalyst are mainly oxygen-containing compounds, and the carbon number of polyols in the products is distributed in the range of 2 to 13, and the proportion of polyols is relatively high.
Claims
1. A method for synthesizing polyols from synthesis gas, characterized in that: The synthesis gas is introduced into the reactor and contacts the iron-based catalyst therein to react at 180-200°C to produce polyols. The reaction pressure is 3.0-5.0 MPa. The feed gas space velocity is 3000-5000 mL / (h∙g cat ) ; The iron-based catalyst is composed of at least Fe5C2 and Fe2C, wherein the mass content of each component is: the active component Fe5C2 content is 43-72%, the active component Fe2C content is 15-28%, and it also contains Fe3O4; The iron-based catalyst is prepared by the following method A or method B: A. Commercial iron oxide pretreatment method, commercial iron oxide includes ferroferric oxide and / or ferric oxide Steps: (1) pre-treating commercial iron oxide powder with a particle size range of 2-500 nm in an air atmosphere at 300-500°C for 3-10 hours to remove impurities on the surface of the iron oxide; (2) pre-treating in a hydrogen flowing atmosphere at 270-500°C for 2-50 hours for reduction; (3) switching to H2 / CO gas, treating at 150-220°C for 1-5 hours to complete carbonization of the iron active component to obtain an iron-based catalyst, wherein the molar ratio of H2 to CO in the H2 / CO gas is 0.05-10; B. Precipitation Method Steps: (1) preparing a soluble iron salt solution, wherein the iron ion concentration in the iron salt solution is 0.02-2.0 mol / L; (2) preparing ammonia water, wherein the ammonia concentration is 1-10 mol / L; (3) adding the ammonia water of step (2) to the iron salt solution of step (1) until the pH value of the solution changes to 9-10; Stir for 30 to 90 minutes, separate the precipitated product by centrifugation or filtration, and wash with distilled water until the pH value of the washed solution is 7 to 8. The washed precipitated product is dried at 60 to 100 ° C for 6 to 24 hours; (4) The dried precipitated product is pretreated in an air atmosphere at 290 to 480 ° C for 3 to 10 hours to remove impurities on the surface of the iron oxide; (5) Pretreatment is performed in a hydrogen flowing atmosphere at 270 to 450 ° C for 2 to 50 hours for reduction; (6) Switch to H2 / CO gas, treat at 150-210 ° C for 1 to 5 hours to complete the carbonization of the iron active component to obtain an iron-based catalyst, and the molar ratio of H2 to CO in the H2 / CO gas is 0.05-10; The synthesis gas is a raw gas containing carbon monoxide and hydrogen, wherein the molar ratio of H2 to CO is 0.5-10, and the raw gas contains no or one or more of the impurity gases CO2, CH4, C2H6, N2, and Ar, and the impurity gas content is less than or equal to 30% of the total volume of the raw gas.
2. The method according to claim 1, characterized in that: The iron-based catalyst also contains a structural additive, which includes one or two of SiO2 and Al2O3. The mass ratio of the structural additive to the total amount of iron-based compounds in the catalyst is 0-25:1, and the iron-based compounds include Fe5C2, Fe2C and Fe3O4. The additive is added to the iron-based catalyst by mixing and grinding with the iron-based compound, or the additive is added to the iron-based catalyst by adding the solution to the precipitation process of preparing the iron-based compound by precipitation method.
3. The method according to claim 2, characterized in that: The mass content of each component of the iron-based catalyst is: the content of active component Fe5C2 is 57-72%, the content of active component Fe2C is 20-26%, and it also contains Fe3O4; The mass ratio of the structural additive to the total amount of the iron-based compounds in the catalyst is 0-0.05:1, and the iron-based compounds include Fe5C2, Fe2C and Fe3O4; The synthesis gas is a raw gas containing carbon monoxide and hydrogen, wherein the molar ratio of H2 to CO is 2-5; When the raw gas contains impurity gas, the impurity gas content is less than or equal to 10% of the total volume of the raw gas.
4. The method according to claim 1, characterized in that: The iron-based catalyst is prepared by the following method A or method B: A. Commercial iron oxide pretreatment method, commercial iron oxide includes ferroferric oxide and / or ferric oxide Steps: (1) Pretreatment of commercial iron oxide powder with a particle size range of 10-100 nm in an air atmosphere at 350-500°C for 4-8 hours to remove impurities on the surface of the iron oxide; (2) Pretreatment in a hydrogen flowing atmosphere at 320-450°C for 5-20 hours for reduction; (3) Switching to H2 / CO gas, treating at 180-210°C for 1-3 hours to complete carbonization of the iron active component to obtain an iron-based catalyst, wherein the molar ratio of H2 to CO in the H2 / CO gas is 0.5-3; B. Precipitation Method Steps: (1) preparing a soluble iron salt solution, wherein the iron ion concentration of the iron salt solution is 0.1-1.5 mol / L; (2) preparing ammonia water, wherein the ammonia concentration is 3-7 mol / L; (3) adding the ammonia water of step (2) to the iron salt solution of step (1) until the pH value of the solution changes to 9-10; The mixture is stirred for 30 to 90 minutes, separated by centrifugation or filtration, and washed with distilled water until the pH value of the washed solution is 7 to 8. The washed precipitate is dried at 60 to 100 °C for 6 to 24 hours. (4) The dried precipitate is pretreated at 350 to 450 °C in an air atmosphere for 4 to 8 hours to remove impurities on the surface of the iron oxide. (5) The precipitate is pretreated at 310 to 430 °C in a hydrogen flowing atmosphere for 4 to 30 hours for reduction. (6) The mixture is switched to H2 / CO gas and treated at 180 to 210 °C for 1 to 3 hours to complete the carbonization of the iron active component to obtain an iron-based catalyst. The molar ratio of H2 to CO in the H2 / CO gas is 0.5 to 3.
5. The method according to claim 1, characterized in that: The soluble iron salt is one or more of nitrate and acetate.
6. The method according to claim 1, characterized in that: Conditions for the reduction step of the iron-based catalyst: atmospheric pressure, H2: 600~3000 mL / (h·g cat ), 270~450℃, time: 2~50h; Carbonization step conditions: 1.0~7.0MPa, synthesis gas: 500~8000 mL / (h·g cat ), the H2 / CO molar ratio in the H2 / CO gas = 0.05~10, the synthesis gas contains or does not contain CO2, and CO2 accounts for 0~10% of the total volume of the gas.
7. The method according to claim 6, characterized in that: The H2 / CO molar ratio in the H2 / CO gas during the carbonization step is 0.5-3.
8. The method according to claim 1, characterized in that: The method can realize the low-temperature direct conversion of synthesis gas into polyols, with the selectivity of alcohol products reaching more than 40%, and polyols accounting for more than 70% of alcohols; the polyols refer to alcohol compounds with a carbon number of 2 to 13 and containing one hydroxyl group.
Citation Information
Patent Citations
Catalyst for preparation of olefins from synthesis gas and by-production of higher alcohols as well as preparation and application of catalyst
CN108067235A